Pengaruh Kesadaran WP, Pelayanan Fiskus, Sanksi Pajak, dan Tax Amnesty Pada Kepatuhan WPOP - Darma Wicaksana, I Gusti Putu Agung; Supadmi, Ni Luh (E-Jurnal Akuntansi; Vol 27 No 3 (2019), 2019)
This study aims to determine the effect of taxpayer awareness, tax authorities, tax sanctions, and tax amnesty on individual taxpayer compliance at the Tabanan Primary Tax Office. This research was conducted at the Tabanan Primary Tax Office. The number of samples taken is 100 taxpayers. The method used is nonprobability sampling, with a purposive sampling technique. Data collection is done by distributing questionnaires and nonparticipant observations. Data were analyzed using multiple linear regression analysis. Based on the results of the study showed that the awareness of taxpayers, tax authorities, tax sanctions, and tax amnesty had a positive effect on the compliance of individual taxpayers at Tabanan Primary Tax Office. The results showed that the awareness of taxpayers, tax authorities, tax sanctions, and the implementation of the tax amnesty policy could increase taxpayer compliance at the Tabanan Primary Tax Office . Keywords : Awareness of the taxpayer, service tax authorities, tax penalties, tax amnesty, taxpayer compliance